Effect of uphill running on VO2, heart rate and lactate accumulation on lower body positive pressure treadmills - Fleckenstein, D.; Ueberschär, O.; Wüstenfeld, J. C.; Rüdrich, P.; Wolfarth, B. (Sports, 2021)
Lower body positive pressure treadmills (LBPPTs) as a strategy to reduce musculoskeletal load are becoming more common as part of sports conditioning, although the requisite physiological parameters are unclear. To elucidate their role, ten well-trained runners (30.2 ± 3.4 years; VO2max: 60.3 ± 4.2 mL/kg/min) ran at 70% of their individual velocity at VO2max (vVO2max) on a LBPPT at 80% body weight support (80% BWSet) and 90% body weight support (90% BWSet), at 0%, 2% and 7% incline. Oxygen consumption (VO2), heart rate (HR) and blood lactate accumulation (LA) were monitored. It was found that an increase in incline led to increased VO2 values of 6.8 ± 0.8 mL/kg/min (0% vs. 7%, p < 0.001) and 5.4 ± 0.8 mL/kg/min (2% vs. 7%, p < 0.001). Between 80% BWSet and 90% BWSet, there were VO2 differences of 3.3 ± 0.2 mL/kg/min (p < 0.001). HR increased with incline by 12 ± 2 bpm (0% vs. 7%, p < 0.05) and 10 ± 2 bpm (2% vs. 7%, p < 0.05). From 80% BWSet to 90% BWSet, HR increases of 6 ± 1 bpm (p < 0.001) were observed. Additionally, LA values showed differences of 0.10 ± 0.02 mmol l-1 between 80% BWSet and 90% BWSet. Those results suggest that on a LBPPT, a 2% incline (at 70% vVO2max) is not yet sufficient to produce significant physiological changes in VO2, HR and LA—as opposed to running on conventional treadmills, where significant changes are measured. However, a 7% incline increases VO2 and HR significantly. Bringing together physiological and biomechanical factors from previous studies into this practical context, it appears that a 7% incline (at 80% BWSet) may be used to keep VO2 and HR load unchanged as compared to unsupported running, while biomechanical stress is substantially reduced.